1999
DOI: 10.1111/1467-6435.00072
|View full text |Cite
|
Sign up to set email alerts
|

Does Growth Cause Happiness, or Does Happiness Cause Growth?

Abstract: The happiness L I I Z~

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 3 publications
2
62
0
10
Order By: Relevance
“…All three low income countries in the sample saw a positive income-SWB relationship -although this is very sparse data which does not allow for properly testing the role of non-income factors. A 1975 cross-country poll reported in Kenny (1999) suggested that there was a significant relationship between income and SWB below a $1000 GNP per capita, and the evidence presented here suggests no reason to lower that barrier (even while the data presented on Tanzania and Calcutta suggests relative and non-income concerns are significant even in the poorest countries). Nonetheless, if improvements in SWB are taken to be a good measure of utility, and increasing utility is the purpose of development, the results suggest that many countries currently considered developing have developed quite enough.…”
Section: Resultsmentioning
confidence: 45%
See 4 more Smart Citations
“…All three low income countries in the sample saw a positive income-SWB relationship -although this is very sparse data which does not allow for properly testing the role of non-income factors. A 1975 cross-country poll reported in Kenny (1999) suggested that there was a significant relationship between income and SWB below a $1000 GNP per capita, and the evidence presented here suggests no reason to lower that barrier (even while the data presented on Tanzania and Calcutta suggests relative and non-income concerns are significant even in the poorest countries). Nonetheless, if improvements in SWB are taken to be a good measure of utility, and increasing utility is the purpose of development, the results suggest that many countries currently considered developing have developed quite enough.…”
Section: Resultsmentioning
confidence: 45%
“…In a recent paper (Kenny, 1999), I found a relationship between economic growth over time within a country and SWB in that country that was not significant in a number of different formulations in a sample of wealthy countries. 3 This confirmed earlier results based on different techniques and samples by (amongst others) Veenhoven (1994) and Easterlin (1995).…”
Section: Income and Happiness Rich And Poormentioning
confidence: 94%
See 3 more Smart Citations